PENGARUH INTERNATIONAL STANDART OF ORGANIZATION, KUALITAS AUDITOR INTERNAL, DAN KONTRAK MANAJEMEN TERHADAP KUALITAS LABA - Sari, Riski Ulan (Universitas Muhammadiyah Tangerang, 2021)
The purpose of this study was to determine the effect of ISO, quality of internal auditors, and management contracts on earnings quality in manufacturing companies listed on the Indonesia Stock Exchange. The time period of the study is 4 years, namely the period 2015-2018. The population of this study includes all manufacturing companies listed on the Indonesia Stock Exchange in the 2015-2018 period. The sampling technique uses purposive sampling technique. Based on predetermined criteria obtained 9 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data regression analysis using the eviews 9.0 data processing program The results showed that ISO has a significant positive effect on earnings quality, while the quality of internal auditors and contract management negatively affects earnings quality.